Microplastic Analysis in the Digestive Tract of Squid (Loligo sp.) Sold at a Traditional Market in Palu City and Its Application as an Educational Medium - Ni Kadek Apriyani; Fatmah Dhafir; Abd. Rauf; Achmad Ramadhan; Moh. Sabran; Masrianih (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to identify the morphological types of microplastics present in the digestive tracts of squid (Loligo sp.) sold at a traditional market in Palu City. A descriptive approach combining quantitative and qualitative analyses was employed. A total of 10 fresh squid specimens were randomly selected from a single vendor at Lasowani Traditional Market. The digestive tracts were isolated, digested using 10% potassium hydroxide (KOH), and incubated at 40°C for 96 h. The recovered particles were subsequently classified and counted, and microplastic abundance was calculated. Three morphological types of microplastics—fibers, films, and fragments—were detected in the digestive tracts of the 10 squid specimens. A total of 948 particles were recorded, corresponding to a mean abundance of 94.8 particles per individual. Films were the most prevalent type, accounting for 48.4% of the total particles, followed by fragments at 26.7% and fibers at 24.9%. These findings indicate that film-type microplastics were dominant in the digestive tracts of the examined squid. Based on the research findings, an educational poster was also developed and subjected to expert validation. The poster achieved a feasibility score of 82.23%, indicating that it was highly suitable, based on the validation results, for use as a learning resource in biology education.